UPAYA MENINGKATKAN HASIL BELAJAR SISWA MATERI PELAJARAN SENI MUSIK DENGAN MENERAPKAN METODE TALKING STICK PADA SISWA KELAS IX 10 SMP NEGERI 13 PEKANBARU TAHUN 2016 - Desmi Erwinda (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2022)
The background of this study is the low ability of students in traditional music art lessons. Cultural arts learning which has only focused on practice so far is not in line with the improvement of students' abilities in theory. This is evident when the researchers held a pre-cycle test for students of class IX 10 of SMP Negeri 13 Pekanbaru which found 11 students only or around 29% who met the KKM graduation criteria from a total of 38 students. This research was conducted in Pekanbaru City precisely in class IX 10 students of SMP Negeri 13 Pekanbaru Academic Year 2016. The purpose of this study was to improve student learning outcomes in arts and culture subjects in class IX 10 Pekanbaru 13 Middle School in 2016 through the talking stick learning strategy. The method used in this study is classroom action research (CAR). This study consisted of several cycles, while each cycle was carried out in 2 meetings. Each cycle consists of steps. Planning / preparation of actions, implementation of actions, observation and reflection. After the results in the first cycle are obtained and have been reflected, improvements are then made to continue the next cycle if needed. The results obtained from the research with this method, namely in the initial stage of a total of 38 students who passed competencies only around 13 students and 29% of students did not pass the KKM. In the first cycle students who graduated from the previous only 11 students or 29%% increased to 32 students or around 84%. Then in cycle II students who graduated increased from 32 students to 37 students or around 97% of a total of 38 students. The conclusion of this class action research is basically students can increase their own interests and abilities but in a condition many obstacles occur so that students have difficulty increasing their abilities. By using the talking stick learning strategy, which is a group learning model with the help of sticks, the group holding the stick must first answer the questions from the teacher after students learn the subject matter, then the activity is repeated continuously until all groups have a turn to answer questions from the teacher. A series of learning activities that emphasize the process of thinking quickly and precisely to answer questions of a problem so students can be trained to think systematically, logically, quickly and critically. Evidenced by the results of each stage of research that increased quite significantly.